Back Pain in Atypical Immediate Hypersensitivity Caused by Exposure to Dust Mites and Molds: A Case Report - Taniguchi, Kazuto; Mizuta, Kazutaka; Uemichi, Kazuyasu (Journal of Nepal Paediatric Society, 2022)
Immediate hypersensitivity to inhaled allergens is common in children. Although wheezing and urticaria are well known in immediate hypersensitivity, back pain is unknown. A nine year old boy with a history of asthma presented with back pain, but not wheezing or urticaria, while wiping the floor. The immuno-capsulated hydrophilic carrier polymer (ImmunoCAP) test revealed that dust mites and molds were the specific antigens causing the immediate hypersensitivity. Therefore, back pain can appear in immediate hypersensitivity. The ImmunoCAP test is useful for determining the allergens in atypical immediate hypersensitivity. Risk factors can be hidden in daily cleaning.